2017
DOI: 10.1177/0003319717738687
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Death in Different Subtypes of Ischemic and Hemorrhagic Stroke

Abstract: Causes of death in both ischemic stroke (IS) and hemorrhagic stroke (HS) subtypes are not comprehensively studied. Between 2008 and 2011, we enrolled 11 215 first-ever stroke patients from the Stroke Registry of Chang-Gung Healthcare System and linked these data to the national death registry. The main causes of death in each stroke subtype were assessed. Patients with HS had higher overall mortality than IS (32.0% vs 18.1%, P < .001). In IS subtypes, large-artery atherosclerosis plus cardioembolism had the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…According to our previous study, 1 more than half of the mortality in HS patients occurred within the first month after stroke onset. Drug switching or discontinuation occurs more commonly within the first 180 days after the start of medication.…”
Section: Methodsmentioning
confidence: 90%
See 3 more Smart Citations
“…According to our previous study, 1 more than half of the mortality in HS patients occurred within the first month after stroke onset. Drug switching or discontinuation occurs more commonly within the first 180 days after the start of medication.…”
Section: Methodsmentioning
confidence: 90%
“… 21 Since coronary artery disease and IS share similar risk factors, IS patients may also be at risk of cardiovascular mortality, particularly the IS subtypes of cardioembolic stroke and large artery disease as seen in our previous study. 1 It is reported that RASI could be beneficial to IS patients, 8 but the benefits to HS patients are undetermined due to HS patients being infrequently enrolled in the previous studies. 8 , 20 , 21 Although RASIs were found to have benefits in animal models with HS, 22 the Scandinavian Candesartan Acute Stroke Trial, which used candesartan in 144 HS patients, only showed conflicting results with possibly harmful effects in the acute phase but neutral effects in the following 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…뇌졸중은 암, 심장병과 함께 주요 사망 원인의 하나로써 유병률이 점차 증가하고 있으며, 생존율은 높아지고 있으 나 기능 장애로 인한 많은 치료비가 지불되고 있다 1,2) . 뇌 의 병변 부위에 따라 손상된 뇌의 반대쪽에 감각 및 운동 장애와 같은 신경학적 손상을 일으키며, 특히 뇌졸중으로 인한 운동결함은 뇌 손상 반대쪽 신체에 발생하는 편마비 가 나타난다 3,4) .…”
Section: 서론»»»unclassified